2023
DOI: 10.3390/polym15061526
|View full text |Cite
|
Sign up to set email alerts
|

A Multiaxial Fracture of Ecoflex Skin with Different Shore Hardness for Morphing Wing Application

Abstract: The use of elastomer-based skins in morphing wings has become increasingly popular due to their remarkable stretchability and mechanical properties. However, the possibility of the skin fracturing during multiaxial stretching remains a significant design challenge. The propagation of cracks originating from flaws or notches in the skin can lead to the specimen breaking into two parts. This paper presents an experimental study aimed at comprehensively evaluating crack propagation direction, stretchability, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The experimental part of the research concerned the material tests necessary to determine the constants in the constitutive equations and the verifying compression test. In order to determine the material constants via four variants, the following tests were carried out: uniaxial tensile test, biaxial tensile test and plane strain tensile test [13,22,23]. The material tests and the conditions for their implementation are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental part of the research concerned the material tests necessary to determine the constants in the constitutive equations and the verifying compression test. In order to determine the material constants via four variants, the following tests were carried out: uniaxial tensile test, biaxial tensile test and plane strain tensile test [13,22,23]. The material tests and the conditions for their implementation are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the material test specimens are succinctly presented in Table 1. As research by Hong et al, Ahmad and Ajaj, and Saini et al indicated, the loading frequency had a remarkable effect on fatigue performance [30][31][32], and the chosen loading frequency adequately covered the strain rate of energy dissipation materials inside seismic damping devices during earthquake actions. For monotonic tests, specimens were firmly secured using wedge jaws on a universal material testing machine equipped with a long-stroke extensometer.…”
Section: Test Arrangements and Designmentioning
confidence: 95%
“…Observing the smooth and gentle way birds of pray sail through the air using their wing-morphing abilities has inspired researchers of all times to create visionary aerodynamic concepts [2][3][4]. The dynamic development of intelligent shape-changing materials in the 21st Century empowered the scientific world to excavate these concepts and adjust them to the economic needs of the current era of aviation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%